Alanine aminotransferase: a clinical and regulatory tool for detecting liver injury-past, present, and future - Senior, J R (Clinical pharmacology and therapeutics, 2012)
Assay of the serum activity of the enzyme alanine aminotransferase (ALT) has become the primary screening tool for detecting acute liver injury. But what does an elevated value mean? Not what it is too often mistakenly believed to indicate. It is not a test of liver function. It does not necessarily predict worse effects to come (in a given person). It is not a valid measure of severity of liver injury or dysfunction. It is too unspecific to be reliable in screening for relatively rare effects on the liver. Although these are substantial limitations, ALT is a very useful biomarker if understood and used properly. It is important to consider how and why these erroneous concepts came to have such wide acceptance, and how elevations of ALT activity for evaluating patients and subjects under study might be interpreted better.